Implementasi Metode Perbandingan Eksponensial (MPE) dalam Pendukung Keputusan Penilaian Kepala Madrasah Terbaik di Kota Mataram - Febri Mamluatul Ulumi; Ria Rismayati (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
The Madrasah Head who has good ability will give the best performance for the Madrasa he leads so that the Madrasa has good quality so that it can create a generation that is smart and has good character and good religion. One of the efforts of the Ministry of Religion of the Republic of Indonesia Mataram City Office to always maintain and improve the quality of Madrasah heads in the City of Mataram is to provide an assessment to choose the best Madrasah head so that all Madrasah heads in the City of Mataram have the motivation to always improve their quality. The design and manufacture of systems in this study use the waterfall methodology. This study uses the Exponential Comparison Method (MPE) which is one of the methods of the Decision Support System (SPK) used to determine the priority order of alternative decisions with multi criteria. The results of this assessment are to get the best Madrasah head ranking table in the city of Mataram based on the results of the system calculation, where these results can already be used by the Ministry of Religion of the Republic of Indonesia Mataram City Office as a consideration in determining the best Madrasa head in the city of Mataram. The conclusion of this study is the construction of a system that is able to produce the best level of Madrasah head assessment in the city of Mataram which can then be used to help the Ministry of Religion of the Republic of Indonesia Mataram City Office in making the decision to determine the best Madrasah head in the city of Mataram effectively and efficiently.